Environment impacts innate immune ontogeny. Issue 1 (January 2017) - Garand, Mathieu; Cai, Bing; Kollmann, Tobias R
Susceptibility to infection and response to vaccination differ between populations and as a function of age. The underlying mechanisms for this age- and population-dependent variation are not known. Specifically, it is unclear if these variations are due to differences in genetically encoded host programs or driven by environmental influences or a combination of both. To address the relationship between gene and environment regarding immune ontogeny, we determined the innate cytokine responses following PRR stimulation of blood mononuclear cells at birth, 1, and 2 yr of age in infants from Caucasian vs . Asian parents and were raised in the same city. At birth, we found that innate cytokine responses were significantly elevated in Asian compared with Caucasian infants. However, these differences waned and responses became more similar over the course of 1–2 yr of living in a similar environment. Our observations that innate response differences present at birth subsequently equalized rather than diverged suggest a key role for environmental effects common to both racial groups in shaping the innate immune responses early in life. Delineating the underlying environmental factors that modulate innate immune responses early in life could provide avenues for targeted beneficial immune modulation.